Ethnomathematics: Rice Procession Faced with Batubara Malays of North Sumatra - Sonya Liani Nasution; Siti Salamah Br Ginting (Universitas Negeri Makassar, 2021)
This study aims to examine the cultural links in a local area with mathematical concepts or commonly known as ethnomathematics. This ethnomathematical research raises the topic of discussion about a